2019
DOI: 10.1111/cod.13444
|View full text |Cite
|
Sign up to set email alerts
|

Filaggrin gene mutations in relation to contact allergy and hand eczema in adolescence

Abstract: Background: Filaggrin is an important protein for structure and function of the skin barrier. Filaggrin gene (FLG) mutations are known to result in dry skin, impaired skin barrier, and increased risk for atopic dermatitis. However, it is not clear whether these mutations are associated with contact allergy or hand eczema in adolescence.Objectives: The purpose of this study was to investigate whether FLG mutations are associated with contact allergy, self-reported hand eczema, or dry skin in adolescence.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…Some studies have found associations, 23,24 while others negate such associations. 10,21,22 Strengths of this experimental study are that it was performed in humans and that the applied skin dose of nickel is known, which allows for understanding of the penetration profile and calculation of the mass balance. Furthermore, the exposure time is longer than in a previous study 10 and is therefore relevant also for occupational settings with high nickel exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have found associations, 23,24 while others negate such associations. 10,21,22 Strengths of this experimental study are that it was performed in humans and that the applied skin dose of nickel is known, which allows for understanding of the penetration profile and calculation of the mass balance. Furthermore, the exposure time is longer than in a previous study 10 and is therefore relevant also for occupational settings with high nickel exposure.…”
Section: Discussionmentioning
confidence: 99%
“…20 Studies of an association between FLG mutations and contact allergy, including nickel allergy, and nickel penetration into skin, however, have shown conflicting results. [21][22][23][24][25] Thus, the role of FLG status in relation to nickel penetration into the skin remains unclear.…”
mentioning
confidence: 99%
“…[15][16][17][18] There are other studies; however, that suggests no such association and that responses to allergens are not changed in individuals with filaggrin loss-of-function mutation. 11,12,19 Mechanism Our current understanding of ACD is that of a 2-phase process that begins with sensitization with a low-molecular-weight allergen or hapten, which is presented by dermal dendritic cells (DCs) to T cells in a proximal draining lymph node. 1,2,20 The DCs involved in hapten recognition and pathogenesis are thought to be Langerhans cells, or myeloid DCs, which produce interleukin (IL)-1b.…”
Section: Role Of Atopymentioning
confidence: 99%
“…38,39 Filaggrin is crucial to the structure and function of the stratum corneum (SC), 40 which provides the physical barrier, and has been shown to be a key player in the pathogenesis of a variety of allergic diseases, 41 and filaggrin gene (FLG) mutations have also been found to be a significant risk factor for allergic diseases such as atopic dermatitis (AD), 42 asthma, allergic rhinitis, FA, 43,44 contact allergy and hand eczema. 45,46 Also, filaggrin gene loss-of-function variants modify the effect of breastfeeding on eczema risk in early childhood. 47 Although filaggrin has been widely known as a key genetic risk factor for AD, 42 it is known to modify AD disease.…”
Section: Filaggrin and Epithelial Barriermentioning
confidence: 99%
“…A dysfunctional epithelial barrier, which allows allergens and microbes to penetrate, leads to the release of type 2 cytokines that drive allergic inflammation and development of anaphylaxis to allergic disease 38,39 . Filaggrin is crucial to the structure and function of the stratum corneum (SC), 40 which provides the physical barrier, and has been shown to be a key player in the pathogenesis of a variety of allergic diseases, 41 and filaggrin gene ( FLG ) mutations have also been found to be a significant risk factor for allergic diseases such as atopic dermatitis (AD), 42 asthma, allergic rhinitis, FA, 43,44 contact allergy and hand eczema 45,46 . Also, filaggrin gene loss‐of‐function variants modify the effect of breastfeeding on eczema risk in early childhood 47 .…”
Section: Milestone Discoveriesmentioning
confidence: 99%